Indications of M-dwarf deficits in the halo and thick disk of the Galaxy - Konishi, Mihoko; Samland, Matthias; Henning, Thomas (Publications of the Astronomical Society of Japan, 2015)
Abstract. We compared the number of faint stars detected in deep survey fields with the current stellar distribution model of the Galaxy and found that the det